Control of oriented cell division in the Arabidopsis embryo. (February 2015) - van Dop, Maritza; Liao, Che-Yang; Weijers, Dolf
Highlights: Oriented cell divisions are crucial for multicellular plant development. It is unclear how developmental regulators control division. The Arabidopsis embryo is a good model for linking development to division control. A framework for genetic and geometric control of division orientation. Abstract : Multicellular plant development requires strict control of cell division orientation. A key unanswered question is how developmental regulators interact with the generic cell division machinery to trigger oriented divisions. We discuss the Arabidopsis embryo as a model for addressing this question. Recent progress in 3D imaging and computation now allows sketching of a framework for the developmental control of division orientation in which the signaling molecule auxin controls oriented division by preventing a geometrically defined default plane. We expect that the identification of auxin effectors, together with the identification of novel regulators of cell division will help to link developmental regulators to the division machinery.